Trends of inflammatory markers and cytokines after one month of phototherapy in patients with rheumatoid arthritis - José Meneses Calderón (Acta Medica Academica, 2015)
Objective. to evaluate changes in the expression of tumor necrosis factor-α in patients with rheumatoid arthritis submitted to phototherapy. Materials and methods. This was an open label study, enrolling ten patients. The phototherapy scheme within a range of 425 to 650 nm, 11.33 Joules/cm2, 30 cm above the chest was as follows: a) 45-min daily sessions from Monday to Friday for 2 to 3 months; b) three, 45min weekly sessions for 1 to 2 months; c) twice weekly 45-min sessions for 1 to 2 months, and d) one weekly session for 1 to 2 months until completion. Erythrocyte sedimentation rate, C-reactive protein and rheumatoid factor were measured in peripheral blood and tumor necrosis factor-α, interleukin-1β, and interleukin-10 in leukocytes by quantitative real-time Reverse transcriptase-Polymerase chain reaction. In all the patients the next indexes: Karnofsky scale, Rheumatoid Arthritis-specific quality of life instrument, Steinbrocker Functional Capacity Rating and the Visual Analog Scale were evaluated. Results. Erythrocyte sedimentation rate, C-reactive protein, and rheumatoid factor declined notoriously after the indicated sessions. In gene expression, there was a tendency in tumor necrosis factor-α to decrease after 1 month, from 24.5±11.4 to 18±9.2 relative units, without reaching a significant statistical difference. The four tested indexes showed improvement. Conclusion. Phototherapy appears to be a plausible complementary option to reduce the inflammatory component in rheumatoid arthritis.